Fatty acid 2-hydroxylation inhibits tumor growth and increases sensitivity to cisplatin in gastric cancerResearch in context - Yizhou Yao; Xiaoqin Yang; Liang Sun; Shishuo Sun; Xiaoheng Huang; Diyuan Zhou; Tingting Li; Wei Zhang; Nada A. Abumrad; Xinguo Zhu; Songbing He; Xiong Su (EBioMedicine, 2019)
Background: Most gastric cancers are diagnosed at an advanced or metastatic stage with poor prognosis and survival rate. Fatty acid 2-hydroxylase (FA2H) with high expression in stomach generates chiral (R)-2-hydroxy FAs ((R)-2-OHFAs) and regulates glucose utilization which is important for cell proliferation and invasiveness. We hypothesized that FA2H impacts gastric tumor growth and could represent a novel target to improve gastric cancer therapy. Methods: FA2H level in 117 human gastric tumors and its association with tumor growth, metastasis and overall survival were examined. Its roles and potential mechanisms in regulating tumor growth were studied by genetic and pharmacological manipulation of gastric cancer cells in vitro and in vivo. Findings: FA2H level was lower in gastric tumor tissues as compared to surrounding tissues and associated with clinicopathologic status of patients, which were confirmed by analyses of multiple published datasets. FA2H depletion decreased tumor chemosensitivity, partially due to inhibition of AMPK and activation of the mTOR/S6K1/Gli1 pathway. Conversely, FA2H overexpression or treatment with (R)-2-OHFAs had the opposite effects. In line with these in vitro observations, FA2H knockdown promoted tumor growth with increased level of tumor Gli1 in vivo. Moreover, (R)-2-OHFA treatment significantly decreased Gli1 level in gastric tumors and enhanced tumor chemosensitivity to cisplatin, while alleviating the chemotherapy-induced weight loss in mice. Interpretation: Our results demonstrate that FA2H plays an important role in regulating Hh signaling and gastric tumor growth and suggest that (R)-2-OHFAs could be effective as nontoxic wide-spectrum drugs to promote chemosensitivity. Fund: Grants of NSF, NIH, and PAPD. Keywords: Fatty acid 2-hydroxylation, Gastric cancer, Lipid metabolism, mTOR, Chemotherapy, Hedgehog pathway